Osteomyelitis post acromioclavicular joint reconstruction - Yeak, Raymond Die Kiat; Daud, Haﬁz; Mohd Nasir, Mohd Nizlan (Elsevier, 2019)
Acromioclavicular joint (ACJ) injury is a common shoulder injury. There are various techniques of ACJ reconstruction. Superﬁcial infection after ACJ reconstruction is not an uncommon complication. However, osteomyelitis post ACJ reconstruction has never been highlighted as a possible complication. Our patient is a 31-year-old male who sustained a Rockwood 5 ACJ dislocation and had anatomical ACJ reconstruction with autogenous gracilis and semitendinosus graft. Our technique involved the anatomical reconstruction of the ACJ and the coracoclavicular ligament with the usage of two bioscrews and the temporary stabilisation of the ACJ with two k-wires. As in any orthopaedic surgery, infection is often disastrous especially when the surgery involves implants. It can be disastrous with high morbidity to the patient as well as a costly complication to treat. Therefore, we wish to highlight this case as despite its rarity, osteomyelitis can be devastating to the patient and should be prevented if possible.